Therapeutic Benefits of Foot Spa for Elderly with Myalgia: A Case Study - Dewi, Gita Ariyani; Darmawati, Irma; Sumartini, Sri (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Myalgia is defined as pain caused by repeated muscle contractions, resulting in muscle inflammation. One of the symptoms of myalgia is the occurrence of pain in the muscles. A non-pharmacological intervention to address myalgia is foot spa therapy. Foot spa therapy involves soaking the feet in warm water with Epsom salt followed by a massage to improve blood circulation and reduce myalgia. Objective: The purpose of this case study is to demonstrate the application of foot spa therapy for elderly individuals with myalgia. Methods: This study used a case study method with two subjects experiencing myalgia. The intervention consisted of foot spa therapy conducted six times over two weeks. Each foot spa session included soaking the feet in warm water for 15 minutes, followed by a 20-minute foot massage. Pain levels were assessed using the Numeric Rating Scale (NRS). Results: The study found that foot spa therapy effectively reduced pain levels from moderate pain (scale 6-5) to mild pain (scale 3-2). Conclusion: Foot spa therapy is effective in reducing myalgia with moderate pain levels. The warm water used in the foot spa contains Epsom salt, which is rich in magnesium sulfate. This mineral is effectively absorbed through the skin, stabilizing muscle contractions by fulfilling the body's mineral requirements. Additionally, the massage component of the foot spa stimulates the release of endorphins, promoting relaxation of muscles and soft tissues in the body.